Pemberdayaan Masyarakat Dalam Penyuluhan Makanan Pendamping ASI di Kelurahan Mangga Kecamatan Medan Tuntungan - Helena Fransysca; Nurdiana Manurung (Indonesian Journal Publisher, 2022)
The importance of proper nutrient intake for children's growth and development is a major concern for parents, providing exclusive breastfeeding until the age of 6 months is a very important first step to ensure children get adequate nutrition for growth and development. At the age of 6 months, the child enters a transition period where the introduction of complementary foods (MP-ASI), MP-ASI is an additional source of nutrition given to children after the age of 6 months to meet their nutritional needs apart from breast milk. The importance of providing complementary foods on time in the age range of 6-12 months is crucial, as children are very vulnerable to malnutrition during this period. Therefore, complementary foods become the main support in maintaining the nutritional balance of children from 6 months to 2 years of age. By providing appropriate complementary foods, it is expected that children can grow and develop optimally and avoid the risk of malnutrition that can interfere with their health and growth.